Analysis of space debris impact source localization based on PVDF piezoelectric film. Issue 1 (1st January 2023) - Tang, Enling; Xie, Chengrui; Guo, Kai; Han, Yafei; Chen, Chuang; Chang, Mengzhou; He, Liping
Abstract: As the pace of human exploration and utilization of space continues to accelerate, space debris gradually becomes an inevitable problem affecting and threatening human space activities. When space debris strikes the spacecraft bulkhead, determining the impact source location timely and accurately is the foundation of the repair damage, and is also of great importance for the safety of astronauts' life. This paper analyzed the wave propagation law in thin plates, established a lightweight sensor array using PVDF (Polyvinylidene fluoride) circular thin-film sensors, and used a two-stage light-gas gun loading system to conduct hypervelocity collision localization experiments on impacting 2A12 aluminum plates to study the effects of sensor array radius and sensor size on localization results. The results show that the smaller the radius of the PVDF sensor array is, the more accurate the positioning result is under the premise of the same size of the PVDF circular film sensor array. On the premise of the same PVDF sensor array arrangement, the larger the PVDF circular membrane sensor is, the more accurate the positioning result is. ABAQUS finite element software is used to study the stress wave propagation of aluminum ball impacting aluminum plate at high speed, simulating space debris impacting spacecraft. The stress waveform obtained from the simulation is in good agreement with the experiment, which shows the accuracy of the numerical simulation method.